2014
DOI: 10.1007/s00429-014-0741-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel form of ciliopathy underlies hyperphagia and obesity in Ankrd26 knockout mice

Abstract: Human ciliopathies are genetic disorders caused by mutations in genes responsible for the formation and function of primary cilia. Some are associated with hyperphagia and obesity (e.g., Bardet–Biedl Syndrome, Alström Syndrome), but the mechanisms underlying these problems are not fully understood. The human gene ANKRD26 is located on 10p12, a locus that is associated with some forms of hereditary obesity. Previously, we reported that disruption of this gene causes hyperphagia, obesity and gigantism in mice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 59 publications
1
24
2
Order By: Relevance
“…However, the underlying molecular mechanisms remain poorly defined343536. Similarly, ANKRD26 mice displayed obesity phenotypes potentially linked to defects in primary cilia37. Finally, mutations in HYLS1 have been detected in individuals with hydrolethalus syndrome38, a putative ciliopathy, and HYLS1 and its worm homologue HYLS-1 have been reported to be required for ciliogenesis in vertebrates and C. elegans , respectively33.…”
Section: Resultsmentioning
confidence: 99%
“…However, the underlying molecular mechanisms remain poorly defined343536. Similarly, ANKRD26 mice displayed obesity phenotypes potentially linked to defects in primary cilia37. Finally, mutations in HYLS1 have been detected in individuals with hydrolethalus syndrome38, a putative ciliopathy, and HYLS1 and its worm homologue HYLS-1 have been reported to be required for ciliogenesis in vertebrates and C. elegans , respectively33.…”
Section: Resultsmentioning
confidence: 99%
“…Ankrd26 is expressed in the CNS, including the hypothalamic ARC and paraventricular nucleus (PVN); in the pancreas and skeletal and smooth muscle cells; in the myocardium; and to a lesser extent in adipose tissue and the liver . A subsequent study revealed that STAT3 phosphorylation in response to leptin in the ARC was similar between Ankrd26 − / − mice and wild‐type littermates . However, the response to α‐melanocyte–stimulating hormone (α‐MSH) that is released from POMC + neurons and signals to melanocortin‐4 receptor (MC4R) in the PVN was significantly reduced.…”
Section: Primary Ciliary Function and Obesitymentioning
confidence: 99%
“…34 A subsequent study revealed that STAT3 phosphorylation in response to leptin in the ARC was similar between Ankrd26 −/− mice and wild-type littermates. 50 However, the response to ␣-melanocyte-stimulating hormone (␣-MSH) that is released from POMC + neurons and signals to melanocortin-4 receptor (MC4R) in the PVN was significantly reduced. Closer investigation revealed that ACIII + cilia were absent from the PVN.…”
Section: Primary Ciliary Function and Obesitymentioning
confidence: 99%
“…In humans, association studies between the MCHR1 gene and parameters of obesity are conflicting, which may be because of epigenetic effects (165) . Studying the obese/hyperphagic Ankrd26-knockout mouse, Acs et al (78) recently demonstrated absence of Adcy3-containing primary cilia in the paraventricular nucleus, a part of the hypothalamus involved in food intake regulation. Similarly, disrupting the function of the Alms1 gene leads to a large decrease of ciliated neurons in the hypothalamus as determined by the absence of Adcy3, Mchr1 and somatostatin receptor 3 (Sstr3) (166) .…”
Section: The Cilium In Neuronal Food Intake Regulationmentioning
confidence: 99%